2020
DOI: 10.1109/access.2020.3033021
|View full text |Cite
|
Sign up to set email alerts
|

On the Minimal Loading of Sensorless Series-Series Compensated Inductive WPT Link Operating at Load Independent Voltage Output Frequency Without Feedback

Abstract: It is well-known that continuous conduction mode (CCM) operation at certain frequency yields nearly load-independent voltage gain in practical series-series compensated inductive wireless power transfer links (SS-IWPTL). Such an operation is usually referred to as "load independent voltage output" (LIVO). Residual load dependence is due to the presence of non-zero equivalent series resistances in both transmitter and receiver. On the other hand, it has been shown that voltage gain remains load-dependent at the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 25 publications
0
11
0
Order By: Relevance
“…This is due to the fact that the simulation model does not include parasitic capacitances of the coils and the diode bridge since they do not affect the first harmonic behavior. In general, if parasitics are brought into the model, the results look much more similar [20]. Here, the first harmonics only are of interest, and it is shown that the first harmonic approximations are quite similar in simulations and experiments.…”
Section: Methodsmentioning
confidence: 59%
See 2 more Smart Citations
“…This is due to the fact that the simulation model does not include parasitic capacitances of the coils and the diode bridge since they do not affect the first harmonic behavior. In general, if parasitics are brought into the model, the results look much more similar [20]. Here, the first harmonics only are of interest, and it is shown that the first harmonic approximations are quite similar in simulations and experiments.…”
Section: Methodsmentioning
confidence: 59%
“…where P O denotes the load power, P O,B signifies load power level corresponding to the bound between CCM and DCM, P O,MIN represents minimum allowed IWPTL load power [20] On the other hand, the relation between the output voltage and load power relation is highly nonlinear yet well-defined analytically in DCM regime (second row of Equation ( 36)). Nevertheless, the relation between the rows of Equation ( 36) is injective (one-to-one), and hence DCM-related output voltage may be estimated from its corresponding CCM counterpart.…”
Section: Correction For Dcm Regimementioning
confidence: 99%
See 1 more Smart Citation
“…Equation ( 8) represents the relationship between the circuit elements to achieve resonance. The parameters I in (9) and V C1 (10) were used for ML training. The coupling value was varied to affect the mutual inductance according to Equation (5) in order to simulate different coupling states between the Tx and Rx.…”
Section: Equivalent Circuit Theoretical Analysismentioning
confidence: 99%
“…Research about Rx-side sensorless WPT systems has been undertaken in [ 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 ]. The study in [ 15 ] proposes a machine learning (ML) assisted method that estimates the power delivered to the Rx by using only measurements at the Tx-side.…”
Section: Introductionmentioning
confidence: 99%